2005
DOI: 10.3736/jcim20050511
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lycium barbarum polysaccharide on tumor microenvironment T-lymphocyte subsets and dendritic cells in H22-bearing mice

Abstract: LBP has anti-tumor effect probably by increasing the numbers of CD4(+) and CD8(+) T cells in TIL to relieve the immunosuppression and enhance the anti-tumor function of the immune system. But whether LBP can recover the phenocyte and function of dendritic cells in H22-bearing mice should be further studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 1 publication
0
24
0
Order By: Relevance
“…Anti-tumor effect of LBP may be caused by increasing the numbers of CD4(+) and CD8(+) T cells in tumor-infiltrating lymphocytes to relieve the immunosuppression and enhance the anti-tumor function of the immune system. However, whether LBP recovers the phenocyte and function of dendritic cells in H22-bearing mice is not known (He et al, 2005). LBP significantly increased the numbers of CD4(+) and CD8(+) T cells in TIL as compared with those in the control group.…”
Section: Antibacterial Effectsmentioning
confidence: 94%
“…Anti-tumor effect of LBP may be caused by increasing the numbers of CD4(+) and CD8(+) T cells in tumor-infiltrating lymphocytes to relieve the immunosuppression and enhance the anti-tumor function of the immune system. However, whether LBP recovers the phenocyte and function of dendritic cells in H22-bearing mice is not known (He et al, 2005). LBP significantly increased the numbers of CD4(+) and CD8(+) T cells in TIL as compared with those in the control group.…”
Section: Antibacterial Effectsmentioning
confidence: 94%
“…Shehuang Xiaoliu Fang, an herbal formula for detoxifying and dissipating masses, is potent to inhibit invasive and adhesive ability of SMMC7721 cells accompanied by increased nm23h1 expression and reduced ICAM1 expression [170] ( Figure 1). [171] . DongChongXiaCao (Cordyceps sinensis), a commonly used herb for tonifying kidney, may increase the expression of major histocompatibility complex class Ⅱ antigens on human hepatoma HA22T/ VGH cells [172] .…”
Section: Inhibition Of Metastasismentioning
confidence: 99%
“…It has a very important role in cellular immunity and humoral immunity. Studies show that LBP has an antitumor effect probably by increasing the number of CD4 + T cells in tumor-infiltrating lymphocytes (TIL) to relieve the immunosuppression and enhance the antitumor function of the immune system (He et al 2005). Research has found that the number of these cells in peripheral blood of patients with esophageal carcinoma was reduced.…”
Section: Effect Of Lbp On Esophageal Cancermentioning
confidence: 99%